Real-time monitoring of peroxiredoxin oligomerization dynamics in living cells - Pastor-Flores, Daniel; Talwar, Deepti; Pedre, Brandán; Dick, Tobias P. (Proceedings of the National Academy of Sciences of the United States of America, 2020)
Peroxiredoxins are central to cellular redox homeostasis and signaling. They serve as peroxide scavengers, sensors, signal transducers, and chaperones, depending on conditions and context. Typical 2-Cys peroxiredoxins are known to switch between different oligomeric states, depending on redox state, pH, posttranslational modifications, and other factors. Quaternary states and their changes are closely connected to peroxiredoxin activity and function but so far have been studied, almost exclusively, outside the context of the living cell. Here we introduce the use of homo-FRET (Förster resonance energy transfer between identical fluorophores) fluorescence polarization to monitor dynamic changes in peroxiredoxin quaternary structure inside the crowded environment of living cells. Using the approach, we confirm peroxide- and thioredoxin-related quaternary transitions to take place in cellulo and observe that the relationship between dimer-decamer transitions and intersubunit disulfide bond formation is more complex than previously thought. Furthermore, we demonstrate the use of the approach to compare different peroxiredoxin isoforms and to identify mutations and small molecules affecting the oligomeric state inside cells. Mutagenesis experiments reveal that the dimer-decamer equilibrium is delicately balanced and can be shifted by single-atom structural changes. We show how to use this insight to improve the design of peroxiredoxin-based redox biosensors.
Gesehen am 08.10.2020